Possible Impact of Reconceptualization of the Eastern Partnership on Further Integration Within the Eu - Brankica Todorovic (CES Working Papers, 2016)
The involvement countries of bilateral and multilateral economic relations, global markets and integration enables the achievement of mutual and multiple benefits which in the case of the Eastern Partnership expressing as security, stability and prosperity, democracy and the rule of law. On the basis of Cost benefit analysis and SWOT analysis, the paper will analyzes the impact of Eastern Partnership on achieving economic objectives of member states of the partnership and the impact of the current situation and issues reconceptualization the mutual relations of partners in foreign trade. As a separate issue the paper analyzes the relationship between the Republic of Serbia with the member countries of the Eastern Partnership in order to detect potential threats and benefits in international exchanges.
Keywords: F10; F13; 330; partnership; integration; foreign trade